Pengaruh Dukungan Orang Tua terhadap Motivasi Belajar Anak Usia Dini Selama Pandemik Covid-19 - Fejriati; supriyadi (Arden Jaya Publisher, 2022)
This study aims to reveal the effect of parental support on early childhood learning motivation during the COVID-19 pandemic. This research is a quantitative research with a survey approach. The population in this study was all early childhood in PAUD Sanggar Learning Activities in North Bekasi. The research sample used a saturated sample with a total sample of 26 young children. Research data obtained through valid and reliable instruments. The test of the parental support instrument obtained an average reliability of 0.891, and the learning motivation instrument obtained a reliability of 0.772. The results showed that parental support had a positive effect on early childhood learning motivation. The implication of this research is that parents are always able to motivate their children in learning during the COVID-19 pandemic by providing maximum support.